Dynamics of self-interacting von Willebrand factor chains in shear flows (2023)
Von Willebrand factor (VWF) is a giant extracellular glycoprotein that performs an essential function during hemostasis. This function includes platelet immobilization, which initiates the platelet plug formation at the primary hemostasis. That immobilization requires both activation and adhesion of VWF on the subendothelial surface, exposed during a vascular injury. VWF is mechanosensitive, and its activation depends on the blood flow velocity. VWF also forms self-aggregates, which are crucial during the immobilization of platelets, but the dynamics of the formation of these self-aggregates remain poorly understood. This thesis theoretically studies how self-interactions affect the flow-induced non-equilibrium conformational dynamics of single or multiple low molecular weight (LMW) VWF multimers. For this purpose, we implemented Brownian dynamics simulations at a coarse-grained (CG) resolution of a bead per VWF domain. First, we study the role of intra-chain interactions in the conformational dynamics of single VWF chains under a shear flow. We contrasted the tuning effect of specific and cohesion interactions on the conformational dynamics of single VWF-like biopolymers. We observe that the impact of cohesion on single chain dynamics was more intense than the effect of the specific interactions despite the equal scale of energies of both interactions. However, introducing a random distribution of specifically interacting domains and increasing the number of these domains improve the tunning effect of these specific interactions in the chain conformational dynamics. We also obtained phase diagrams that show the dependence of chain extension probability on each intra-chain interaction energy and external shear rate for different values of the density of specific interacting domains. Second, we examined a system consisting of multiple VWF-like self-interacting chains interacting under a shear flow and able to interact with a surface. Instead of specific A1-A2 interactions, we introduced a surface interaction that enhances the adhesion of a bead that mimics one of the VWF domains (A3), which adheres to the subendothelial surface of a blood vessel. Our systematic analysis reveals that chain-chain and chain-surface interactions coexist non-trivially to modulate the spontaneous adsorption of VWF and the posterior immobilization of secondary tethered chains. Accordingly, these interactions tune VWF's extension and propensity to form shear-assisted functional adsorbed aggregates. Our data highlights VWF self-interacting chains' collective behavior when bound to the surface, distinct from that of isolated or flowing chains. Furthermore, we show that the extension and the exposure to solvent have a similar dependence on shear flow at a VWF-monomer level of resolution. Overall, our results highlight the complex interplay between adsorption, cohesion, and shear forces and the relevance of that interplay for the adhesive hemostatic function of VWF. Third, we simulate the entire unfolding process of the VWF A2 domain in a CG GoMARTINI approach with beads of the size of chemical functional groups. Next, we use the same approach to study VWF A2-A2 interactions between three A2 domains using constant pulling forces miming shear flow conditions. Low pulling forces are enough to create a protrusion in one of the A2 domains and to start an interaction with another collapsed A2 domain. In contrast, higher pulling forces completely elongate all the A2 domains, making the simultaneous interaction between one domain and the other two domains possible. We could express this new information about A2-A2 specific interactions and A2-unfolding in a resolution of one bead per VWF domain to introduce both effects in our modeling of VWF self-interacting multimers. However, we leave that improvement in our model for later studies.